1994
DOI: 10.1007/bf00370713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the dystrophic forms of epidermolysis bullosa: mutations in the type VII collagen gene

Abstract: Significant progress has recently been made in understanding the molecular basis of heritable skin diseases, such as epidermolysis bullosa, a group of mechano-bullous genodermatoses. In particular, the dystrophic forms of epidermolysis bullosa have been shown to result from distinct mutations in the gene encoding type VII collagen, the major, if not the exclusive, component of the anchoring fibrils. These mutations result in deficient synthesis and/or altered assembly of the anchoring fibrils, thus compromisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…The pathogenesis of DEB involves a basement membrane zone (BMZ)-specific collagen called type VII collagen, the major component of structures within the BMZ called anchoring fibrils. DEB patients have defects in the gene, designated COL7A1, that encodes for type VII (anchoring fibril) collagen (2). The BMZ of patients with DEB is characterized by a paucity or diminutive size of anchoring fibrils (3).…”
Section: Dystrophic Epidermolysis Bullosa (Deb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of DEB involves a basement membrane zone (BMZ)-specific collagen called type VII collagen, the major component of structures within the BMZ called anchoring fibrils. DEB patients have defects in the gene, designated COL7A1, that encodes for type VII (anchoring fibril) collagen (2). The BMZ of patients with DEB is characterized by a paucity or diminutive size of anchoring fibrils (3).…”
Section: Dystrophic Epidermolysis Bullosa (Deb)mentioning
confidence: 99%
“…The BMZ of patients with DEB is characterized by a paucity or diminutive size of anchoring fibrils (3). Earlier genetic linkage studies identified the human COL7A1 as the gene responsible for DEB (2, 4 -6), and then numerous COL7A1 gene defects were directly identified in families of patients with DEB (2).…”
Section: Dystrophic Epidermolysis Bullosa (Deb)mentioning
confidence: 99%
“…RDEB is caused by mutations in the COL7A1 gene that encodes type VII collagen, the major component of anchoring fibrils (AFs) that tether together the 2 main layers of skin, the epidermis and dermis (2,3). With insufficient type VII collagen and AFs, the adherence between the epidermis and dermis is compromised and subepidermal blistering from minor trauma ensues.…”
Section: Introductionmentioning
confidence: 99%
“…14 Mutations or deficiencies of collagen type VII as in bullous systemic lupus erythematosus or dystrophic forms of EB 15 result in a paucity of collagen type VII anchoring collagen fibrils 16 leading to skin fragility and extensive blistering. Patients with skin basement membrane disorders constantly suffer from severe blisters and recurring wounds throughout the body and associated infections.…”
Section: Introductionmentioning
confidence: 99%